Analytical strategies for identification and quantitation of heterodimers in co-formulated monoclonal antibody cocktails by native SEC-MS - Wenjing Peng; Yuetian Yan; Victoria C. Cotham; Andrew Heindel; Shunhai Wang; Ning Li (Scientific Reports)
Abstract Co-formulation of two or more therapeutic monoclonal antibodies (mAbs) into one final drug product has gained significant popularity recently due to its numerous advantages, including enhanced efficacy, reduced overall adverse events, and improved patient convenience and compliance. However, the increased heterogeneity of mAb cocktails introduces additional challenges for both formulation development and analytical characterization. Specifically, the identification and quantitation of various dimer species in mAb cocktails is particularly challenging due to their low abundances and highly similar biophysical properties. Traditional analytical tools used for dimer analysis in mAb monotherapy products often lack the specificity needed to distinguish between heterodimers and homodimers. In this study, we report the development and evaluation of a size-exclusion chromatography method coupled to online native mass spectrometry (nSEC-MS) for analyzing dimers in mAb cocktails. Various sample treatment strategies, such as deglycosylation and immunodepletion, were developed to facilitate the differentiation and quantitation of dimer species in two- and three-mAb cocktails. Additionally, key parameters in SEC separation (e.g., flow rate) and MS data acquisition (e.g., resolution settings) were explored to improve method throughput and sensitivity. Together, this optimized nSEC-MS method and associated analytical strategies were demonstrated to be highly effective in identification and quantitation of various hetero- and homodimer species and can be widely applied to support the development of mAb cocktail products.